Respostas
respondido por:
2
É só multiplicar x vezes x
x vezes 1
-1 vezes x
e -1 vezes 1
vai ficar x ao quadrado+1x-1x-1=2x^2
corta o -1x e +1x
x^2 (quer dizer x ao quadrado)
fica x^2-1=2x^2
-1=2x^2-x^2
-1=x^2
x=\/1 \/(raiz)
x=1
x vezes 1
-1 vezes x
e -1 vezes 1
vai ficar x ao quadrado+1x-1x-1=2x^2
corta o -1x e +1x
x^2 (quer dizer x ao quadrado)
fica x^2-1=2x^2
-1=2x^2-x^2
-1=x^2
x=\/1 \/(raiz)
x=1
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás